Teacher Attitude and Inclusion in Primary Education - Chutia, Manoj Kumar Chutia (THE PRIMARY TEACHER, 2022)
Inclusion is a term recently brought into use in education all over the world. This idea has evolved from the concept of equal educational opportunity to all children without any discrimination. It is an approach to bring all children including Children with special needs ‘together under the same umbrella for educational purposes, so that children with disabilities can participate as fulltime learners in any neighbouring school with adequate support systems. However, teachers’ positive frame of mind is essential for making inclusion effective and successful. In this paper an attempt has been made to study primary Teachers’s Attitude Towards Inclusive Education (TASTIE)